The Role of Customer Engagement Influenced Brand Image, Advertising, and Patient Experience on Customer Delight of Outpatients in Hospital X - Palit, Selvyana C.; Indrawati, Ratna; Pamungkas, Rian Adi (Alta Dharma Publisher, 2025)
Background: This research originates from a preliminary survey indicating that while most BSD area residents are aware of Hospital X, there is potential to enhance both the quality of its services and the extent of its utilization within the community. Objective: The aim of this study was to examine brand image, advertising, and patient experience on customer delight, with customer engagement serving as a mediating variable among Hospital outpatient population. Method: The study employed a quantitative approach using a cross-sectional design. The target population included all patients who had received care at Hospital X's Internal Medicine outpatient department in the past six months, though the exact number of patients is unknown. Using purposive sampling and the Lemeshow formula, 99 respondents were selected. Data was gathered through questionnaires and analyzed using the three-box method combined with multiple linear regression. Result: The findings demonstrate that brand image, advertising, and patient experience influence customer delight, with customer engagement as a mediating factor. However, brand image and advertising do not significantly affect customer engagement or customer delight among Hospital X's outpatients. Conversely, patient experience has a notable direct impact on both customer engagement and customer delight. Additionally, customer engagement directly enhances customer delight. Conclusion: Patient experience emerges as the most influential factor in boosting customer engagement and delight, whereas advertising is the least impactful in achieving these outcomes